2020
DOI: 10.1371/journal.pntd.0008017
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei invades the olfactory nerve and bulb after epithelial injury in mice and causes the formation of multinucleated giant glial cells in vitro

Abstract: The infectious disease melioidosis is caused by the bacterium Burkholderia pseudomallei. Melioidosis is characterised by high mortality and morbidity and can involve the central nervous system (CNS). We have previously discovered that B. pseudomallei can infect the CNS via the olfactory and trigeminal nerves in mice. We have shown that the nerve path is dependent on mouse strain, with outbred mice showing resistance to olfactory nerve infection. Damage to the nasal epithelium by environmental factors is common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 113 publications
0
30
0
Order By: Relevance
“…Within a mammalian host, Bpm is a facultative intracellular pathogen that can invade and survive within nearly all cell types, phagocytic and nonphagocytic alike [ 9 , 10 ]. Whitely et al demonstrated the ability of Bpm and the closely related BSL2 pathogen Burkholderia thailandensis to establish an infection in a variety of primary cell lines and noted that the bacteria thrived in bronchial epithelial and vein endothelial cells, suggesting these locations as possible in vivo colonization sites [ 9 ].…”
Section: Bpm Pathogenesis Process Leading To Mnmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a mammalian host, Bpm is a facultative intracellular pathogen that can invade and survive within nearly all cell types, phagocytic and nonphagocytic alike [ 9 , 10 ]. Whitely et al demonstrated the ability of Bpm and the closely related BSL2 pathogen Burkholderia thailandensis to establish an infection in a variety of primary cell lines and noted that the bacteria thrived in bronchial epithelial and vein endothelial cells, suggesting these locations as possible in vivo colonization sites [ 9 ].…”
Section: Bpm Pathogenesis Process Leading To Mnmentioning
confidence: 99%
“…Central nervous system (CNS) involvement is relatively rare in human melioidosis but more common in chronic murine models. It has been demonstrated that Bpm invades the olfactory bulb and can fuse glial cells [ 10 ]. Micro-abscesses in the white matter and thickening of the trigeminal nerve has been observed in human patients with CNS melioidosis, suggesting that Bpm invades the CNS through axon transport and bypassing the blood–brain barrier [ 53 ].…”
Section: Future Directions and Modelsmentioning
confidence: 99%
“…The glial cells of the olfactory nerve (OECs) are hypothesized to be the key phagocytes in this nerve, and to play key roles in the protection against microorganisms ( Harris et al., 2009 ; Panni et al., 2013 ; Nazareth et al., 2015 ). The ability to infect and survive inside OECs, rather than being phagocytosed and degraded by the cells, is thought to be a feature of microorganisms that can invade the primary olfactory nervous system ( Macedo-Ramos et al., 2016 ; Walkden et al., 2020 ). Trigeminal nerve Schwann cells (TgSCs) can also phagocytose microorganisms ( Panni et al., 2013 ), however, Schwann cells have also been shown to express lower levels of mRNA for innate immune factors ( Vincent et al., 2005 ) and to mount a far weaker immune response to bacteria ( Vincent et al., 2007 ) than OECs.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells, however, have been shown to exhibit a significantly lower immune response to pathogens than OECs ( Vincent et al., 2007 ). Some of the bacteria that can invade the olfactory/trigeminal nerves have been shown to infect rather than be cleared by OECs/TgSCs, including S. pneumoniae ( Macedo-Ramos et al., 2016 ), B. pseudomallei ( Walkden et al., 2020 ), and N. meningitidis ( Delbaz et al., 2020 ). Thus, one possibility by which Chlamydia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Within a mammalian host, Bpm acts as an intracellular pathogen that has been shown to invade and survive within nearly all cell types and tissues; phagocytic and nonphagocytic alike [9,10,32]. Whitely et al, demonstrated the ability of Bpm and the closely related BSL2 pathogen B. thailandensis to establish an infection in a variety of primary cell lines and noted that the bacteria thrived particularly in bronchial epithelial and vein endothelial cells; suggesting those locations as possible unidentified in vivo colonization sites [9].…”
Section: Bpm Pathogenesis Process Leading To Mngc Formationmentioning
confidence: 99%